Counter-narratives in modern Arabic poetry (Saeed Al-Zubaidi as an example) (Journal of the College of Basic Education, 2025)
This research is based on studying counter-narratives in Saeed Al-Zubaidi's poetry. It is necessary to identify the term counter-narratives, what is meant by it in modern literary criticism, and how it appeared in Saeed Al-Zubaidi's poetry through history, heritage and religion, and whether the poet employed it correctly. Narration seeks to create a space for dialogue and discussion, by presenting multiple points of view. The poet can motivate the reader to think critically and interact with the text in a deeper way. This type of narration does not only aim to convey ideas.